Implication of one-way direction using schedule time at Jalan Indera Mahkota 5, Kuantan, Pahang - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah (AIP Publishing, 2024)
Beginning March 8, 2021, the public works department Jabatan Kerja Raya (JKR) Kuantan, implemented a one-way direction according to a scheduled time at Jalan Indera Mahkota 5. Observations confirmed that the one-way direction according to the scheduled time caused traffic congestion during peak hours. The objective of this study is to analyze the percentage of vehicles that do not obey the one-way directions according to the scheduled time and analyze road user compliance based on responses to a questionnaire. Traffic study and questionnaire are the methods used in this study. The traffic study is divided into two categories: the total number of vehicles and the percentage of vehicles that do not obey the one-way direction at a scheduled time. The findings of this study indicate that 12% of the vehicles did not follow JKR’s instructions. The results from the questionnaires show that 80% of the respondents did not notice the signboard installed and 53% of the respondents agreed to have the road routes changed from scheduled one-way direction to full-time one-way direction. The recommendation of this study is to resize the signboard to an appropriate size so that it can be seen by road users from a sufficiently further distance. Furthermore, the statistical results of this study were provided to JKR Kuantan for further action.